Where are Iraq’s Poor? : Mapping Poverty in Iraq - Vishwanath, Tara; Sharma, Dhiraj; Krishnan, Nandini; Blankespoor, Brian (World Bank, Washington, DC, 2015)
Measuring poverty and tracking it over time is an important prerequisite to national economic planning. Absence of official data on household expenditure or poverty line hampered the ability of Iraqi policymakers to understand the extent of the problem, analyze their causes, and devise appropriate policies. Iraq household socioeconomic survey (IHSES) 2006-07 was the first survey of its kind since 1988 to cover all 18 governorates. The survey collected rich information on income, expenditure, employment, housing, education, health, and other socioeconomic indicators. Building on the experience of the first IHSES survey and using international best practice on sampling and questionnaire design and survey implementation, the second round of IHSES was fielded in 201-/13. To fill the data gap, a larger survey was designed to collect information on correlates of household welfare like demographic characteristics, education, occupation, housing, and assets and estimate small-area poverty rates using projection methods. This report presents results from the exercise, the first of its kind for Iraq. Poverty mapping not only provides a visual representation of poverty at subnational levels, it also reveals pockets of poverty and islands of prosperity where they exist. This knowledge is useful to inform decisions on policy design and targeting of development projects and programs.